Healthy ageing despite chronic pain: the role of formal social support for functional autonomy and dependence - Matos, Marta Alexandra Osório de (2017)
Chronic pain is prevalent and bears a toll on older adults’ lives. Pain-related disability is the major cause of functional disability amongst older adults, and (formal) social support may play a central role in overcoming the detrimental effects of pain experiences. The literature on the effects of pain-related support on pain-related disability has shown inconsistent results. It is this thesis contention that the extent to which pain-related formal social support (e.g., received from caregivers at day-care centres, nursing homes) constitutes a protective or a risk factor regarding pain-related disability depends on the extent to which it promotes functional autonomy (perceived promotion of autonomy) or dependence (perceived promotion of dependence). In order to provide empirical support to such contention, a measure of these concepts – the revised Formal Social Support for Autonomy and Dependence in Pain Inventory- was developed and validated (study 1). Then, the direct association between perceived promotion of autonomy/dependence and pain-related disability and its behavioural and psychological mediating mechanism were investigated (studies 2 and 3). Finally, the buffering/amplifying effects of perceived promotion of autonomy/dependence on the effect of pain intensity on pain-related disability were analysed (study 4). Findings confirmed that perceived promotion of autonomy has a protective role and perceived promotion of dependence is as risk factor to pain-related disability. Also, these two functions of social support act through different pathways. This thesis provides insight on the role of pain-related support and bears important practical implications by informing formal caregivers’ practices on which support actions can lead to better outcomes.